Biomarkers in stable coronary heart disease, their modulation and cardiovascular risk: The LIPID biomarker study. (15th December 2015) - Tonkin, Andrew M.; Blankenberg, Stefan; Kirby, Adrienne; Zeller, Tanja; Colquhoun, David M.; Funke-Kaiser, Anne; Hague, Wendy; Hunt, David; Keech, Anthony C.; Nestel, Paul; Stewart, Ralph; Sullivan, David R.; et al.
Abstract: Aims: In patients with stable coronary heart disease (CHD), we aimed to assess 1. the prognostic power of biomarkers reflecting haemodynamics, micronecrosis, inflammation, coagulation, lipids, neurohumoral activity, and renal function; 2. whether changes in concentrations of these biomarkers over 12 months affected subsequent CHD risk; and 3. whether pravastatin modified the change in biomarker concentrations and this influenced the risk of future events. Methods: In the LIPID study, 9014 patients were randomised to pravastatin 40 mg or placebo 3–36 months after an acute coronary syndrome. Eight biomarkers were measured at baseline ( n  = 7863) and 12 months later ( n  = 6434). Results: During a median of 6.0 (IQR 5.5–6.5) years follow-up, 1100 CHD-related deaths and nonfatal myocardial infarctions occurred, 694 after biomarker measurement at 12 months. Baseline BNP, CRP, cystatin C, D-dimer, midregional pro-adrenomedullin, and sensitive troponin I predicted recurrent CHD events. In a multivariable model, sensitive troponin I, BNP, and cystatin C had the strongest associations with outcome ( P  < 0.001 for trend). The strongest improvement in risk prediction was achieved by including sensitive troponin I (net reclassification improvement (NRI) 5.5%; P  = 0.003), BNP (4.3%; P  = 0.02), history of MI (NRI 7.0%; P  < 0.001). In landmark analyses, among biomarkers, changes to 12 months in sensitive troponin I (HR 1.32 (1.03–1.70) for T3/T1), BNP (HR 1.37 (1.10–1.69) for Q4/Q1) and Lp-PLA2 (HR 1.52 (1.16–1.97)) improved CHD risk prediction. Conclusions: Baseline levels and changes in sensitive troponin I, and BNP may have the potential to guide the intensity of secondary prevention therapy. Graphical abstract: Potential pathophysiological pathways (in addition to lipid-related mechanisms) modifying the risk of coronary heart disease events in the LIPID study. *NRI = net reclassification improvement. For comparison, the NRIs for conventional risk factors are 7.0% for previous myocardial infarction, 3.2% for male sex, and 2.9% for older age.